2018
DOI: 10.1108/ict-03-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Employer branding and talent retention: perceptions of employees in higher education institutions in Uganda

Abstract: Purpose The purpose of this paper is to examine, empirically the relationship between employer branding attributes of reward strategy, people orientedness and; leadership and development on talent retention in institutions of higher learning in Uganda. Design/methodology/approach In a cross-sectional study, data were obtained form 218 respondents from two public universities. Confirmatory factor analysis (CFA) and structural equation modeling were employed to analyze the data. Findings The paper has two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 42 publications
(38 reference statements)
6
67
0
3
Order By: Relevance
“…External employer brand focuses on prospective applicants whom the organization are willing to give roles and responsibilities. Research on external employer brand is limited to the study on prospective employee attraction (Alshathry, Clarke, & Goodman, 2017; Arriscado, Quesado, & Sousa, 2019; Banerjee, Saini, & Kalyanaram, 2018; Hadi & Ahmed, 2018; Kucherov & Zamulin, 2016; Maheshwari, Gunesh, Lodorfos, & Konstantopoulou, 2017; Matongolo, Kasekende, & Mafabi, 2018; Saini, Gopal, & Kumari, 2015; Saini, Rai, & Choudhary, 2014; Sokro et al, 2012). On the other hand, internal-oriented employer brand focuses on the existing employees (Hochegger, 2014), that is, those who are experiencing the brand and will act as brand ambassadors of the organization.…”
Section: Review Of Literature and Research Gapmentioning
confidence: 99%
“…External employer brand focuses on prospective applicants whom the organization are willing to give roles and responsibilities. Research on external employer brand is limited to the study on prospective employee attraction (Alshathry, Clarke, & Goodman, 2017; Arriscado, Quesado, & Sousa, 2019; Banerjee, Saini, & Kalyanaram, 2018; Hadi & Ahmed, 2018; Kucherov & Zamulin, 2016; Maheshwari, Gunesh, Lodorfos, & Konstantopoulou, 2017; Matongolo, Kasekende, & Mafabi, 2018; Saini, Gopal, & Kumari, 2015; Saini, Rai, & Choudhary, 2014; Sokro et al, 2012). On the other hand, internal-oriented employer brand focuses on the existing employees (Hochegger, 2014), that is, those who are experiencing the brand and will act as brand ambassadors of the organization.…”
Section: Review Of Literature and Research Gapmentioning
confidence: 99%
“…Addressing the importance of EB, a survey reported that Indian companies have started to recognize the power of EB, where nearly 72% of responding companies consider EB as a top priority (Backhaus, 2016). EB as a human resource tool has been a topic of interest among various researchers, where the power of EB has been researched continuously and has also been evident to significantly impact employees’ interest levels (Matongolo et al, 2018; Tanwar, 2016; Tanwar & Prasad, 2016b).…”
Section: Introductory Backgroundmentioning
confidence: 99%
“…This has necessitated the employers to devise strategies that attract and retain the pool of talented employees (Marginson, 2011). As earlier stated, the present employers have started to invest in showcasing them as a great place to work via EB (Matongolo et al,2018;Hamidizadeh and Mohammadnezhad Fadardi, 2019). It is required that employers should understand the nuance of unique attributes of CSR, career advancement, and quality of work-life, among others while implementing an effective EB strategy (Kumari and Saini, 2018;Carlini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In context to higher education institutions (Bendaraviciene, 2015), identified teamwork, job satisfaction, work-life balance, and supervisor relationship to be mostly manifested in the higher education industry. Similarly, a study reported that when higher education institutions adopt reward and people-oriented strategies, they succeed in retaining employees for a longer duration (Matongolo, Kasekende and Mafabi, 2018).…”
Section: Literature Reviewmentioning
confidence: 95%